Community Action for Climate Change and Sustainable Development: Some Lessons for Kerala and Tamil Nadu from around the world (Global Journal of Human-Social Science, 2025)
Climate change is markedly intensifying the challenges associated with urban heat, especially within rapidly growing Indian cities such as Kerala and Tamil Nadu. This study critically examines community action as a pivotal mechanism driving climate change mitigation and sustainable urban development. Leveraging an integrated analysis of both global and local case studies, it delves into the multifaceted impacts of rising urban heat. Particular focus is placed on health risks linked to elevated nocturnal temperatures, exacerbation of the urban heat island effect, and heightened vulnerability among marginalized populations. Employing a robust mixed-methods methodology encompassing literature review, case studies, and stakeholder interviews, the research identifies critical gaps in climate data accessibility, policy harmonization, and community inclusiveness. Findings substantiate the effectiveness of localized, community-driven initiatives in amplifying resilience and adaptive capacity. The study culminates with tangible recommendations emphasizing multi-sector collaboration, enhanced climate modelling, and inclusive frameworks necessary to safeguard vulnerable urban residents amid escalating climate threats.